Experiencia sobre educación rural en el municipio de Samacá, Boyacá. Colombia - María Cecilia Rodríguez-Rueda; Marco Antonio Piñeros-Piñeros (Revista Electrónica Educare)
The author describes the experience of working with rural communities and its educational institutions developed by the Rural Education Investigative. Group of Universidad Pedagógica y Tecnologica de Colombia, since 1999 at the municipality of Samaca, Boyacá. This experience had two stages; the first one gathered the socio cultural and pedagogical characteristics, in a holistic vision, of the families living in Guantoque, Páramo Central y Gacal areas. The second stage of the experience is based on the results obtained and searches through the investigation-social projection, the design and carrying out of an alternative proposal in pedagogy and health primary attention, which contributes to improve the living conditions of children and their families. The methodology used is based in the investigation-action paradigm, and has being adopted by teachers, parents, municipal institutions and organizations, as well as the administration and secretary of education of the municipality.